Effects of fructooligosaccharide administration routes on growth performance, gut integrity, microbiota, and meat quality in broiler chickens exposed to reused litter - Y. Ruangpanit; Konkawat Rassmidatta; Ananchai Philatha; Prayooth Saothong; Chokchai Sompugdee; P. Phungkeha; Kanokrat Srikijkasemwat; Kazeem Dauda Adeyemi; Rasheed O. Sulaimon; Panneepa Sivapirunthep; Chanporn Chaosap (Poultry Science, 2025)
This study investigated the effects of dietary fructooligosaccharide (FOS) supplementation, administered via feed or drinking water, on growth performance, gut morphology, microbiota, stress response, and meat quality in broiler chickens reared under reused litter conditions. A total of 900 one-day-old male Ross 308 chicks were randomly allocated to three groups: a control (CON), 0.5 % FOS in drinking water (FOS-W), and 0.5 % FOS in feed (FOS-F), over a 38-day trial conducted using reused litter to simulate oxidative and physiological stress. FOS administration route had no significant effect on growth performance, carcass characteristics, gut morphology, cecal microbiota composition, stress indicators, meat quality, or ribonucleotide levels. Furthermore, FOS supplementation, irrespective of delivery method, did not influence growth, carcass traits, or meat quality when compared to the control. However, both FOS-supplemented groups exhibited significantly higher villus height-to-crypt depth ratios in the ileum and jejunum, increased cecal Lactobacillus counts, and reduced heterophil-to-lymphocyte ratios, indicating enhanced intestinal integrity and reduced physiological stress. In conclusion, while FOS supplementation did not affect performance or meat quality under reused litter conditions, it positively influenced gut morphology, microbial balance, and stress response. These findings support the potential of FOS as a functional feed additive to improve intestinal health and resilience in broiler chickens under intensive production systems.
Keywords: Animal Nutrition and Physiology; Agriculture, Soil, Plant Science